Socializing Models During Lactation Alter Colonic Mucosal Gene Expression and Fecal Microbiota of Growing Piglets - Bi, Yanju; Wei, Haidong; Nian, Haoyang; Liu, Runze; Ji, Wenbo; Liu, Honggui; Bao, Jun (Frontiers in Microbiology, 2022)
The enrichment of the social environment during lactation alleviates the stress of weaned piglets. It is significant to understand how the enriched social environment improves the weaning stress of piglets. RNA sequencing (RNA-seq) of colonic mucosa, 16S rRNA sequencing of feces, and short-chain fatty acids (SCFAs) of colonic content were used to determine the effects of social contact during lactation. In this study, thirty litters of lactating piglets were divided into intermittent social contact (ISC) group that contacted with neighbors intermittently, continuous social contact (CSC) group that contacted with neighbors starting at day (D) 14 after birth, and control (CON) group in which piglets were kept in their original litter. The piglets were weaned at D35 and regrouped at D36. The colonic mucosal RNA-seq, fecal microbes, and SCFAs of colonic contents of 63-day-old piglets were analyzed. The results of RNA-seq showed that compared with the CON group, the pathways of digestion and absorption of minerals, protein, and vitamins of piglets were changed in the ISC group, while the pathways of retinol metabolism and nitrogen metabolism in the colonic mucosal were affected and stimulated the immune response in the CSC group. Compared with the CON group, the abundances of pernicious microorganisms (Desulfovibrio, Pseudomonas, Brevundimonas, etc.) in the CSC group, pernicious microorganisms (Desulfovibrio, Neisseria, Sutterella, etc.) and beneficial bacteria (Bifidobacterium, Megamonas and Prevotella_9) in the ISC group were significantly higher (P < 0.05). The abundances of pro-inflammatory bacteria (Coriobacteriaceae_unclassified, Coprococcus_3, and Ruminococcus_2) in the CSC group were significantly increased (P < 0.05), but the abundances of SCFAs producing bacteria (Lachnospiraceae_UCG-010, Parabacteroides, Anaerotruncus, etc.) and those of anti-inflammatory bacteria (Eubacterium, Parabacteroides, Ruminiclostridium_9, and Allprevotella) were significantly reduced (P < 0.05) in the CSC group. Compared with the CON group, the concentrations of microbial metabolites, acetate and propionate in the colonic contents were reduced (P < 0.05) in the ISC group, while the concentration of acetate was reduced (P < 0.05) in the CSC group. Therefore, both ISC and CSC during lactation affected the composition of fecal microbes and changed the expression of intestinal mucosal genes related to nutrient metabolism and absorption of piglets.